G-C3N4 / TiO2 fiber catalyst as well as preparation method and application thereof
By preparing g-C3N4/TiO2 fiber catalysts, the problems of difficult recycling of powder photocatalysts and secondary pollution of water bodies were solved, achieving efficient catalytic decomposition of dye wastewater and reducing costs.
Patent Information
- Application Number
- CN202411432850.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-10
AI Technical Summary
Existing powder photocatalysts are difficult to recycle, leading to secondary water pollution and high costs.
The g-C3N4/TiO2 fiber catalyst was prepared by electrospinning and high-temperature calcination, and then combined with melamine and TiO2 fibers to form the g-C3N4/TiO2 fiber catalyst.
It achieves highly efficient catalytic decomposition of dye wastewater, with a degradation efficiency of over 98%, reducing operating costs and preventing catalyst from entering the water body and causing secondary pollution.
Smart Images

Figure CN119281364A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fiber catalyst preparation, and in particular to a g-C3N4 / TiO2 fiber catalyst and a preparation method and application thereof. Background Art
[0002] With the development of the times and technology, energy crisis and environmental pollution are two major issues for modern society to maintain sustainable development. Among the wastewater in the textile industry, dye wastewater accounts for 80% of the discharge. Due to its high organic content, complex composition, large chromaticity and poor biodegradability, it is extremely harmful. Therefore, the degradation of organic pollutants is particularly important.
[0003] For the treatment of dye wastewater, traditional treatment technologies include physical method, chemical method and biological method. Although the traditional treatment methods for printing and dyeing wastewater have been mature and used on a large scale, they still have the defects of poor treatment effect or complicated process and difficult to control. Photocatalytic oxidation method is to use light in the presence of catalyst to produce free radicals with strong oxidizing ability in the reaction system to degrade and remove organic matter. Because of its advantages such as fast reaction speed, high degradation efficiency and no secondary pollution, it is considered to be a sustainable means of treating synthetic dye pollutants.
[0004] Most traditional photocatalysts are in powder form. When they photocatalytically decompose organic matter in sewage, they will be lost during the treatment process, resulting in a decrease in the catalytic reaction rate and an increase in the cost of photocatalytic degradation of dye wastewater. Based on this, a g-C3N4 / TiO2 fiber catalyst was developed, which can not only efficiently catalyze and decompose dyes in water, but also is easy to recycle. This not only reduces operating costs, but also prevents the catalyst from entering the water and causing secondary pollution to the water. Summary of the invention
[0005] In view of this, the present invention provides a g-C3N4 / TiO2 fiber catalyst and a preparation method and application thereof, in order to solve the problems of existing powder photocatalysts being difficult to recycle, prone to secondary water pollution and high cost.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The present invention provides a method for preparing a g-C3N4 / TiO2 fiber catalyst, comprising the following steps:
[0008] Tetrabutyl titanate, a water-soluble high molecular polymer and a solvent are mixed and stirred at low temperature to obtain a spinning solution; the spinning solution is subjected to electrostatic spinning to obtain titanium dioxide fibers.
[0009] Melamine and TiO2 fibers that have passed through a 500-mesh sieve are placed in a container and transferred to a muffle furnace for high-temperature calcination to obtain a g-C3N4 / TiO2 fiber catalyst.
[0010] Preferably, the water-soluble high molecular polymer is one or more of polyvinyl pyrrolidone, polyacrylamide, polyvinyl alcohol, polymethyl methacrylate and polyethylene oxide.
[0011] Preferably, the solvent is independently a mixture of ethanol and acetic acid, the concentration of acetic acid is independently 0.5-3.5%, and the mass ratio of ethanol to acetic acid is independently 4-4.8:1.
[0012] Preferably, in the step of preparing the spinning solution, the mass ratio of tetrabutyl titanate to the solvent is 1:4 to 4.6.
[0013] Preferably, in the step of preparing the spinning solution, the mass ratio of tetrabutyl titanate to the water-soluble polymer is 1:1.5-2.5, and the mass ratio of the mixture of tetrabutyl titanate and the water-soluble polymer to the solvent is 1:5-8.
[0014] Preferably, the stirring is carried out under low temperature conditions, with a temperature of 10 to 25° C., a stirring time of 1 to 24 h, and a stirring rate of 350 to 800 r / min.
[0015] Preferably, the voltage of the electrospinning is independently 12 to 25 kV, the translation speed of the electrospinning spinneret is independently 120 to 280 mm / min, the translation stroke of the electrospinning is independently 300 to 500 mm, the vertical distance between the electrospinning spinneret and the collecting drum is independently 12 to 25 cm, and the rotation speed of the collecting drum is independently 80 to 350 r / min.
[0016] Preferably, the melamine is in the lower layer of the container, and the TiO2 fibers are placed in the upper layer of the container, and the distance between the upper and lower layers is 10 to 15 cm.
[0017] Preferably, the melamine is crushed by a crusher, and the rotation speed of the crusher is 12000-19000 rpm.
[0018] Preferably, the mass ratio of melamine to TiO2 fiber is 4-6:1.
[0019] Preferably, the calcination is carried out in a muffle furnace at a temperature of 500 to 700° C. and a calcination time of 3 to 6 hours.
[0020] The present invention also provides a g-C3N4 / TiO2 fiber catalyst prepared by the preparation method of the g-C3N4 / TiO2 fiber catalyst.
[0021] The present invention also provides the use of the g-C3N4 / TiO2 fiber catalyst in treating dye wastewater, wherein the printing and dyeing wastewater is a mixture of dye and water; the dye is one or more of methyl orange, methylene blue, rhodamine B, phenol, bisphenol A, crystal violet and Congo red.
[0022] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0023] The g-C3N4 / TiO2 fiber catalyst obtained by the present invention can treat various dye wastewaters, and the photocatalytic decomposition effect of various dye pollution reaches more than 98%, which greatly improves the application range of the g-C3N4 / TiO2 fiber catalyst and has excellent wastewater treatment effect;
[0024] The g-C3N4 / TiO2 fiber catalyst of the present invention has a simple preparation process, mild reaction conditions, no need for large-scale equipment, and saves costs, providing a new idea for the preparation of catalysts required for dye wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0026] Figure 1 This is a scanning electron microscope image of the TiO2 fiber obtained in Example 1 of the present invention;
[0027] Figure 2 This is the XRD pattern of the g-C3N4 / TiO2 fiber catalyst obtained in Example 1 of the present invention; DETAILED DESCRIPTION
[0028] The present invention provides a method for preparing a g-C3N4 / TiO2 fiber catalyst, comprising the following steps:
[0029] Tetrabutyl titanate, a water-soluble high molecular polymer and a solvent are mixed and stirred at low temperature to obtain a spinning solution; the spinning solution is subjected to electrostatic spinning to obtain titanium dioxide fibers.
[0030] Melamine and TiO2 fibers that have passed through a 500-mesh sieve are placed in a container and transferred to a muffle furnace for high-temperature calcination to obtain a g-C3N4 / TiO2 fiber catalyst.
[0031] In the present invention, the water-soluble high molecular polymer is preferably one or more of polyvinyl pyrrolidone, polyacrylamide, polyvinyl alcohol, polymethyl methacrylate and polyethylene oxide.
[0032] In the present invention, the solvent is independently a mixture of ethanol and acetic acid, and the concentration of acetic acid is independently preferably 0.5-3.5%, and more preferably 0.8-3.3%; the mass ratio of ethanol to acetic acid is independently preferably 4-4.8:1, and more preferably 4.2-4.7:1.
[0033] In the present invention, in the step of preparing the spinning solution, the mass ratio of tetrabutyl titanate to the solvent is preferably 1:4 to 4.6, and more preferably 1:4.1 to 4.5.
[0034] In the present invention, in the step of preparing the spinning solution, the mass ratio of tetrabutyl titanate to the water-soluble polymer is preferably 1:1.5-2.5, and more preferably 1:1.6-2.4; the mass ratio of the mixture of tetrabutyl titanate and the water-soluble polymer to the solvent is preferably 1:5-8, and more preferably 1:5.2-7.6.
[0035] In the present invention, the low-temperature stirring is carried out, the temperature is preferably 10-25°C, more preferably 12-24°C; the stirring time is preferably 1-24h, more preferably 5-20h; the stirring rate is preferably 350-800r / min, more preferably 380-750r / min.
[0036] In the present invention, the voltage of the electrospinning is independently preferably 12 to 25 kV, and more preferably 14 to 22 kV; the translation speed of the electrospinning spinneret is independently preferably 120 to 280 mm / min, and more preferably 140 to 260 mm / min; the translation stroke of the electrospinning is independently preferably 300 to 500 mm, and more preferably 320 to 480 m; the vertical distance between the electrospinning spinneret and the collecting drum is independently preferably 12 to 25 cm, and more preferably 14 to 22 cm; the rotation speed of the collecting drum is independently preferably 80 to 350 r / min, and more preferably 90 to 330 r / min.
[0037] In the present invention, the electrospinning is carried out using a syringe; the specification of the syringe is preferably 1-20 mL, and more preferably 5-15 mL; the inner diameter of the needle in the syringe is preferably 0.39-0.43 mm, and more preferably 0.4-0.42 mm; the outer diameter of the needle in the syringe is preferably 0.58-0.75 mm, and more preferably 0.62-0.69 mm; the injection speed of the syringe is preferably 0.2-0.5 mm / min, and more preferably 0.25-0.45 mm / min.
[0038] In the present invention, the melamine is in the lower layer of the container, and the TiO2 fiber is placed in the upper layer of the container. The distance between the upper and lower layers is preferably 10 to 15 cm, and more preferably 10.5 to 14.5 cm.
[0039] In the present invention, the melamine is crushed by a crusher, and the rotation speed of the crusher is preferably 12000-19000 rpm, and more preferably 13000-18500 rpm.
[0040] In the present invention, the mass ratio of melamine to TiO2 fiber is preferably 4-6:1, and more preferably 4.2-5.8:1.
[0041] In the present invention, the calcination is carried out in a muffle furnace, the calcination temperature is preferably 500-700° C., more preferably 550-680° C.; the calcination time is 3-6 hours, more preferably 3.5-5.8 hours.
[0042] The present invention also provides a g-C3N4 / TiO2 fiber catalyst prepared by the preparation method of the g-C3N4 / TiO2 fiber catalyst.
[0043] The present invention also provides the use of the g-C3N4 / TiO2 fiber catalyst in treating printing and dyeing wastewater, characterized in that the printing and dyeing wastewater is a mixture of dye and water; the dye is one or more of methyl orange, methylene blue, rhodamine B, phenol, bisphenol A, crystal violet and Congo red.
[0044] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0045] Example 1
[0046] 1 g of tetrabutyl titanate, 10.3 g of anhydrous ethanol, 1.6 g of polyvinyl pyrrolidone and 2.46 g of 3.3% acetic acid solution were weighed and mixed, and stirred at 15° C. for 18 h at a speed of 450 r / min to obtain a spinning solution.
[0047] A 10 mL syringe with a needle having an inner diameter of 0.41 mm and an outer diameter of 0.71 mm was used to extract the spinning solution for electrospinning to obtain TiO2 fibers;
[0048] The electrospinning parameters for preparing TiO2 fibers are as follows: the electrospinning voltage is 18 kV, the injection speed is 0.4 mm / min, the receiving device is coated with aluminum foil on the receiving roller, the distance between the spinning needle and the receiving roller is 20 cm, the rotation speed of the receiving roller is 120 r / min, the electrospinning needle translation speed is 250 mm / min, the electrospinning translation stroke is 450 mm, the spinning temperature is 25 ° C, and the relative humidity is 35%.
[0049] The melamine raw material was crushed by a crusher at a speed of 14000rpm, and then processed through a 500-mesh sieve to obtain melamine. 4.5g of melamine and 1g of TiO2 fiber were weighed, and the melamine was placed in the lower layer of the container, and the TiO2 fiber was placed in the upper layer of the container, with a distance of 14cm between the upper and lower layers. It was then transferred to a muffle furnace for calcination at a temperature of 550°C and a calcination time of 5.5h to obtain a g-C3N4 / TiO2 fiber catalyst.
[0050] The g-C3N4 / TiO2 fiber catalyst obtained in this example was used to degrade printing and dyeing wastewater containing methyl orange, and the degradation efficiency was above 98%.
[0051] Example 2
[0052] 2 g of tetrabutyl titanate, 24.82 g of anhydrous ethanol, 3.4 g of polyacrylamide and 5.77 g of 3.1% acetic acid solution were weighed and mixed, and stirred at 14° C. at a speed of 700 r / min for 20 h to obtain a spinning solution.
[0053] A 10 mL syringe with a needle having an inner diameter of 0.42 mm and an outer diameter of 0.72 mm was used to extract the spinning solution for electrospinning to obtain TiO2 fibers;
[0054] The electrospinning parameters for preparing TiO2 fibers are as follows: the electrospinning voltage is 22 kV, the injection speed is 0.4 mm / min, the receiving device is coated with aluminum foil on the receiving roller, the distance between the spinning needle and the receiving roller is 16 cm, the rotation speed of the receiving roller is 130 r / min, the electrospinning needle translation speed is 240 mm / min, the electrospinning translation stroke is 420 mm, the spinning temperature is 25 ° C, and the relative humidity is 35%.
[0055] The melamine raw material was crushed by a pulverizer at a speed of 15000rpm, and then processed through a 500-mesh sieve to obtain melamine. 4.8g of melamine and 1g of TiO2 fiber were weighed, and the melamine was placed in the lower layer of the container, and the TiO2 fiber was placed in the upper layer of the container, with a distance of 13.5cm between the upper and lower layers. It was then transferred to a muffle furnace for calcination at a temperature of 580°C and a calcination time of 5.5h to obtain a g-C3N4 / TiO2 fiber catalyst.
[0056] The g-C3N4 / TiO2 fiber catalyst obtained in this example was used to degrade printing and dyeing wastewater containing methylene blue, and the degradation efficiency was above 98%.
[0057] Example 3
[0058] 3 g of tetrabutyl titanate, 44 g of anhydrous ethanol, 5.4 g of polyvinyl alcohol and 10 g of 3.1% acetic acid solution were weighed and mixed, and stirred at 13° C. for 18 h at a speed of 650 r / min to obtain a spinning solution.
[0059] A 5 mL syringe with a needle having an inner diameter of 0.41 mm and an outer diameter of 0.71 mm was used to extract the spinning solution for electrospinning to obtain TiO2 fibers;
[0060] The electrospinning parameters for preparing TiO2 fibers are as follows: the electrospinning voltage is 21 kV, the injection speed is 0.4 mm / min, the receiving device is coated with aluminum foil on the receiving roller, the distance between the spinning needle and the receiving roller is 17 cm, the rotation speed of the receiving roller is 115 r / min, the electrospinning needle translation speed is 230 mm / min, the electrospinning translation stroke is 400 mm, the spinning temperature is 25°C, and the relative humidity is 35%.
[0061] The melamine raw material was crushed by a crusher at a speed of 14000rpm, and then processed through a 500-mesh sieve to obtain melamine. 5.2g of melamine and 1g of TiO2 fiber were weighed, and the melamine was placed in the lower layer of the container, and the TiO2 fiber was placed in the upper layer of the container, with a distance of 11.5cm between the upper and lower layers. It was then transferred to a muffle furnace for calcination at a temperature of 560°C and a calcination time of 5.4h to obtain a g-C3N4 / TiO2 fiber catalyst.
[0062] The g-C3N4 / TiO2 fiber catalyst obtained in this example was used to degrade printing and dyeing wastewater containing Rhodamine B, and the degradation efficiency was above 98%.
[0063] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a g-C3N4 / TiO2 fiber catalyst, characterized in that: The steps include: Tetrabutyl titanate, a water-soluble high molecular polymer and a solvent are mixed and stirred at low temperature to obtain a spinning solution; the spinning solution is subjected to electrostatic spinning to obtain titanium dioxide fibers. Melamine and TiO2 fibers that have passed through a 500-mesh sieve are placed in a container and transferred to a muffle furnace for high-temperature calcination to obtain a g-C3N4 / TiO2 fiber catalyst.
2. The method for preparing the g-C3N4 / TiO2 fiber catalyst according to claim 1, characterized in that: The water-soluble high molecular polymer is one or more of polyvinyl pyrrolidone, polyacrylamide, polyvinyl alcohol, polymethyl methacrylate and polyethylene oxide.
3. The method for preparing the g-C3N4 / TiO2 fiber catalyst according to claim 2, characterized in that: The solvent is independently a mixed solution of ethanol and acetic acid, the concentration of acetic acid is independently 0.5-3.5%, and the mass ratio of ethanol to acetic acid is independently 4-4.8:
1.
4. The method for preparing the g-C3N4 / TiO2 fiber catalyst according to claim 1 or 3, characterized in that: In the step of preparing the spinning solution, the mass ratio of tetrabutyl titanate to the solvent is 1:4 to 4.
6.
5. The method for preparing the g-C3N4 / TiO2 fiber catalyst according to claim 1 or 2, characterized in that: In the step of preparing the spinning solution, the mass ratio of tetrabutyl titanate to the water-soluble high molecular polymer is 1:1.5-2.5, and the mass ratio of the mixture of tetrabutyl titanate and the water-soluble high molecular polymer to the solvent is 1:5-8.
6. The method for preparing the g-C3N4 / TiO2 fiber catalyst according to any one of claims 1 to 3, characterized in that: The stirring is carried out under low temperature conditions, the temperature is 10-25° C., the stirring time is 1-24 hours, and the stirring rate is 350-800 r / min.
7. The method for preparing the g-C3N4 / TiO2 fiber catalyst according to claim 6, characterized in that: The voltage of the electrospinning is independently 12-25 kV, the translation speed of the electrospinning spinneret is independently 120-280 mm / min, the translation stroke of the electrospinning is independently 300-500 mm, the vertical distance between the electrospinning spinneret and the collecting roller is independently 12-25 cm, and the rotation speed of the collecting roller is independently 80-350 r / min.
8. The method for preparing the g-C3N4 / TiO2 fiber catalyst according to claim 1, characterized in that: The melamine is placed in the lower layer of the container, and the TiO2 fiber is placed in the upper layer of the container, and the distance between the upper and lower layers is 10-15 cm.
9. The method for preparing the g-C3N4 / TiO2 fiber catalyst according to claim 1 or 8, characterized in that: The melamine is crushed by a crusher, and the rotation speed of the crusher is 12000-19000 rpm.
10. The method for preparing the g-C3N4 / TiO2 fiber catalyst according to claim 1 or 9, characterized in that: The mass ratio of the melamine to the TiO2 fiber is 4-6:
1.
11. The method for preparing the g-C3N4 / TiO2 fiber catalyst according to claim 1 or 10, characterized in that: The calcination is carried out under the conditions of the muffle furnace, the calcination temperature is 500-700° C., and the calcination time is 3-6 hours.
12. The g-C3N4 / TiO2 fiber prepared by the method for preparing the g-C3N4 / TiO2 fiber catalyst according to any one of claims 1 to 11.
13. The use of the g-C3N4 / TiO2 fiber catalyst in treating printing and dyeing wastewater according to claim 12, characterized in that: The printing and dyeing wastewater is a mixture of dye and water; the dye is one or more of methyl orange, methylene blue, rhodamine B, phenol, bisphenol A, crystal violet and Congo red.